2022
DOI: 10.1007/s10483-022-2896-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulating absence seizures by tri-phase delay stimulation applied to globus pallidus internal

Abstract: In this paper, a reduced globus pallidus internal (GPI)-corticothalamic (GCT) model is developed, and a tri-phase delay stimulation (TPDS) with sequentially applying three pulses on the GPI representing the inputs from the striatal D 1 neurons, subthalamic nucleus (STN), and globus pallidus external (GPE), respectively, is proposed. The GPI is evidenced to control absence seizures characterized by 2 Hz-4 Hz spike and wave discharge (SWD). Hence, based on the basal ganglia-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Many researchers suggested that stimulation targeting subthalamic nucleus (STN) and globus pallidus interna (GPi) (Hou et al., 2022) can improve the motor symptoms of patients. However, they usually ignore the role of globus pallidus (GPe) in the central brain region of the basal ganglia, and stimulating GPe may have a similar effect.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers suggested that stimulation targeting subthalamic nucleus (STN) and globus pallidus interna (GPi) (Hou et al., 2022) can improve the motor symptoms of patients. However, they usually ignore the role of globus pallidus (GPe) in the central brain region of the basal ganglia, and stimulating GPe may have a similar effect.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the mean-field model, DBS is simulated as the applied electric field generated by the stimulation electrode (fig. 1(a)) [19][20][21][22][23]. The specific modeling method is shown in the following two equations:…”
mentioning
confidence: 99%
“…φ DBS is the input pulse that stimulates an electric field generated by an electrode. This modeling method is used to explore the effect of DBS on absence epilepsy, focusing on the modulation effect of external stimulation on spike and slow-wave discharges [21][22][23]. Wang et al investigated the impact of coordinated reset stimulation (CRS), which involves intermittent pulsed currents applied to the cortex, specific relay nucleus (SRN), and thalamic reticular nucleus (TRN), on the control of absence seizures using a cortical-thalamic mean-field model [21].…”
mentioning
confidence: 99%